2015
DOI: 10.3329/bmrcb.v40i3.25228
|View full text |Cite
|
Sign up to set email alerts
|

Role of ascitic fluid adenosine deaminase (ADA) and serum CA-125 in the diagnosis of tuberculous peritonitis

Abstract: This cross sectional study was carried out in the department of gastroenterology, BIRDEM, Dhaka from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Previous studies reported that serum CA125 levels are detected to be elevated in all patients with TBP compared to healthy controls (6,17). CA125 was found to have 83.33% sensitivity in the diagnosis of clinically suspected TBP (18). In our study, CA125 was positive in 85.42% of patients, which is consistent with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported that serum CA125 levels are detected to be elevated in all patients with TBP compared to healthy controls (6,17). CA125 was found to have 83.33% sensitivity in the diagnosis of clinically suspected TBP (18). In our study, CA125 was positive in 85.42% of patients, which is consistent with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis found that ADA level of ascites fluid above 39 IU/L was reliable to diagnose peritoneal tuberculosis with 100% sensitivity and 97.2% specificity [23]. This finding was supported by numerous study [16, 18, 24].…”
Section: Discussionmentioning
confidence: 70%
“…Specific symptomsfever (84.6%)Physical examinationCommon physical examination results of both diseases• abdominal mass• ascites• abdominal tenderness• weight loss (underweight) [30]No single specific physical examination to differentiate abdominal TB and Ovarian Malignancy), following signs tend to be presented in one disease, but can be found in the other under specific condition• Solid organ enlargement (hepatomegaly, splenomegaly, or hepatosplenomegaly)• Inguinal lymphadenopathy• Localised adnexal mass (in early stage)• Pleural effusion (advanced stage)• Liver metastasis (advanced stage) [31]Abdominal UltrasoundCommonCystic massSpecific• Ascites (free or loculated, clear or complex with membranes, septum, or debris)• Peritoneal or omental thickening• Lymph node involvement (periportal, peripancreatic, mesenteric, or retroperitoneal• Bowel wall thickening or distended fluid-filled bowel loops.• Abdominal abscesses• Visceral involvement: homogeneous organomegaly, focal lesion, or calcified foci [32]• Presence of ascites• Peritoneal masses (nodular), enlarged nodes, or matted bowel [33]• Solid part that is often nodular or papillary• Irregular, thick septations• Color or power Doppler demonstration of flow in the solid component [33]. Abdominal CT scanCommonCystic massSpecific• Free or loculated ascites• Smooth thickening of the peritoneum• Lymph nodes enlargement with central necrosis and calcification• Thickening of the mesentery and omentum• Homogenous organomegaly [34]• Primary ovarian mass• Multinodular and irregular peritoneal thickening• Homogeneous retroperitoneal lymph nodes enlargement• Omental cake• Hepatic and splenic focal metastatic lesion [34, 35]Common additional testsCA-125Increased [79, 15]Increased [12, 13]HE4Increased (≤151.4 pmol/l) [14]Markedly increased (>151.4 pmol/l) [10, 1214]Specific Additional testsSpecific Additional tests• Polymerase chain reaction for mycobacterium of ascites fluid [18, 36]• Xpert MTB/RIF assay of sputum or tissue biopsy [20, 29]• Amino deaminase test of ascites fluid [23, 24]• T-cell-based interferon gamma release assay (IGRA) of ascites fluid or blood […”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum CA-125 levels (> 35 U/mL) and adenosine deaminase activity (ADA) of ascitic fluid (> 30 U/l) have been proposed as easy, non-invasive tests for peritoneal tuberculosis with high sensitivity and specificity (respectively 83% and 50% for CA-125 and 93% and 94% for ADA) [ 12 , 13 ].Therefore measuring ADA levels is recommended in the diagnostic work-up for peritoneal tuberculosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%